2019
DOI: 10.1186/s12879-019-4679-7
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal myiasis followed by tracheal-esophageal fistula: report of a rare case and literature review

Abstract: BackgroundTo enhance awareness of the clinical features and prevention of endotracheal myiasis.Case presentationA case of intratracheal myiasis is reported. A 61-year-old male patient with a history of laryngectomy was admitted to hospital due to tracheostomal hemorrhage of 3 h duration. Intratracheal myiasis was confirmed by bronchoscopy, and the patient underwent bronchoscopic intervention, which was complicated by a tracheal-esophageal fistula and resolved by endotracheal stenting. Twenty months after stent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…6,8 Moreover, if not treated timely, tracheostomal myiasis may cause severe complications, including secondary infection, respiratory failure, tracheal stenosis, trachea-esophageal perforations, and thromboembolization of adjoining vessels. 5,10 In conclusion, tracheostomal myiasis can occur in children with long-term tracheostomy, albeit rarely.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…6,8 Moreover, if not treated timely, tracheostomal myiasis may cause severe complications, including secondary infection, respiratory failure, tracheal stenosis, trachea-esophageal perforations, and thromboembolization of adjoining vessels. 5,10 In conclusion, tracheostomal myiasis can occur in children with long-term tracheostomy, albeit rarely.…”
mentioning
confidence: 92%
“…[2][3][4] Tracheostomal myiasis is a rare clinical entity and extremely rare in paediatric population. [2][3][4][5][6][7] In a massive internet search using PubMed/Medline services, authors could find only 3 cases reported in children on the cited subject. 6,8,9 Myiasis is classified as specific (obligate), semi-specific (facultative), and accidental (pseudomyiasis).…”
mentioning
confidence: 99%